Designing user-centered policy for social robotics: policy analysis and consultation with the aging and dementia community. - Dosso, Jill A.; Martin, Susanna E.; Ye, Haiger; Guerra, Gabriella K.; Riminchan, Anna; Robillard, Julie M. (Disability & Rehabilitation: Assistive Technology, 2025)
Purpose: Social robots are a promising assistive technology to support older adults in home and healthcare environments. Engaging end-users in all stages of social robot research, development, and deployment is critical to adoption. However, the voices of end-users are missing from policies about social robots. This work consults with end-users of social robots to capture their perspectives on social robot policies and co-create expert-driven policy recommendations to guide the future implementation of social robots for aging. Materials and Methods: In this two-part study, we performed a content analysis of n = 47 international policies on social robotics followed by seventeen semi-structured interviews with experts on aging and dementia from both professional (n = 6) and lived experience (n = 11) perspectives to capture their opinions about social robot policies. Results: Our analysis highlights alignments between social robot policy recommendations and perspectives of the dementia community including upholding respect for human rights and dignity, the need for clear and consistent regulation, and the need for public engagement. Participants further recommended that policies should prioritize cost and accessibility considerations and focus on aging- and dementia-specific considerations. Participants reported that the responsibility for social robot policy development lay primarily with governments and the healthcare sector. Increased consultation with end-users, minority groups and medical professionals was suggested for future policy development. Conclusion: Findings contribute to the ethical co-creation of social robots as assistive technologies for older adults and provide actionable steps for the development of policies that reflect the values and perspectives of end-users. IMPLICATIONS FOR REHABILITATION: Social robots are promising assistive devices for older adults and persons living with dementia, including in cognitive rehabilitation contexts, but there is a lack of clear, consistent regulation in how these devices should be designed and used. Older adults and aging and dementia experts are eager to participate in robot co-design as it relates to rehabilitation. There is an ethical imperative to engage these and other end-user groups in the development of robots and robot policy. Current social robotics policies focus on challenges to adoption and ethical issues such as discrimination, bias, deception, inequality, and liability. Persons with lived experiences of dementia and professional experts point out policy gaps around cost and access, the involvement of minority groups and end-users in policymaking, a lack of standardization, and a lack of aging- and dementia-specific considerations. There is rapid development happening at the intersection of social robotics and rehabilitation; and while the policy landscape is not yet equipped to manage these emerging issues, empirical evidence such as the findings in this paper can support next steps in this area.